2021
DOI: 10.1002/ece3.8017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spawning Pacific salmon on terrestrial invertebrates: Insects near spawning habitat are isotopically enriched with nitrogen‐15 but display no differences in body size

Abstract: When Pacific salmon ( Oncorhynchus spp.) spawn and die, they deliver marine‐derived nutrient subsidies to freshwater and riparian ecosystems. These subsidies can alter the behavior, productivity, and abundance of recipient species and their habitats. Isotopes, such as nitrogen‐15 ( 15 N), are often used to trace the destination of marine‐derived nutrients in riparian habitats. However, few studies have tested for correlations between stable isotopes and physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
3
2
0
Order By: Relevance
“…Finally, 50-150% increases in δ 15 N values were observed in benthic macroinvertebrates along gradients of increasing anthropogenic nutrient enrichment in Sweden (Bergfur et al 2009;, similar to observations elsewhere (Clapcott et al 2010;Smucker et al 2018). Differences in δ 13 C values in the same studies ranged less widely, from 0 to 9% (anthropogenic nutrient enrichment, Bergfur et al 2009;, 0-4% (marine derived nutrients, Hocking and Reimchen 2002;Rammell et al 2021) and 0-1% (river restoration, Kupilas et al 2020). Collier et al (2002) observed a more marked 28-31% difference in δ 13 C values between an agricultural compared with forested catchment in New Zealand, which is attributable to strong differences in tree cover that were not a factor in our study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Finally, 50-150% increases in δ 15 N values were observed in benthic macroinvertebrates along gradients of increasing anthropogenic nutrient enrichment in Sweden (Bergfur et al 2009;, similar to observations elsewhere (Clapcott et al 2010;Smucker et al 2018). Differences in δ 13 C values in the same studies ranged less widely, from 0 to 9% (anthropogenic nutrient enrichment, Bergfur et al 2009;, 0-4% (marine derived nutrients, Hocking and Reimchen 2002;Rammell et al 2021) and 0-1% (river restoration, Kupilas et al 2020). Collier et al (2002) observed a more marked 28-31% difference in δ 13 C values between an agricultural compared with forested catchment in New Zealand, which is attributable to strong differences in tree cover that were not a factor in our study.…”
Section: Discussionsupporting
confidence: 74%
“…Riparian spider δ 15 N values were 9% higher in an agricultural compared with forested catchment in New Zealand (Collier et al 2002), and river restoration was associated with 7-11% increases in δ 15 N values of riparian spiders and beetles (Kupilas et al 2020). More marked 70-400% shifts in δ 15 N values were observed in detritivorous millipedes, omnivorous beetles and predatory spiders living adjacent to rivers with marine-salmon-derived nutrient enrichment, relative to references (Hocking and Reimchen 2002;Rammell et al 2021). Finally, 50-150% increases in δ 15 N values were observed in benthic macroinvertebrates along gradients of increasing anthropogenic nutrient enrichment in Sweden (Bergfur et al 2009;, similar to observations elsewhere (Clapcott et al 2010;Smucker et al 2018).…”
Section: Discussionsupporting
confidence: 69%
“…The seed output of hemiparasitic Castilleja species can be influenced by their host species via changes in alkaloid uptake and herbivory-pollination feedbacks [ 47 ]. The lack of effect in three of the focal species is also consistent with research demonstrating that the presence of salmon-derived nitrogen-15 is often decoupled from meaningful biological consequence for individual organisms [ 54 , 55 ].…”
Section: Discussionsupporting
confidence: 78%
“…A likely explanation is that lower trophic‐level organisms (e.g., plants) uptake nutrients over smaller areas, and are therefore more affected by characteristics of their local environment, while higher trophic‐level taxa (e.g., songbirds) forage over larger areas, likely spanning multiple locations both within and among islands. Indeed, a similar study found riparian soil and herbivorous weevils to have higher levels of δ 15 N closer to salmon‐bearing streams, but δ 15 N of more mobile, carnivorous beetles was unaffected (Rammell et al, 2021). We also found that 15 N enrichment drops off more rapidly with increasing distance to shore on larger islands.…”
Section: Discussionmentioning
confidence: 98%